Can cattle blood be transformed into an organic source of nitrogen? - Md. Islam; S. M. Zaman; Md. Rasel; Jagadish Joardar (International Journal of Recycling of Organic Waste in Agriculture)
Purpose: A study was conducted to transform bovine blood, a slaughterhouse by-product, into an organic source of nitrogen, which is otherwise disposed of through sewer systems only to pollute the nearby water bodies.   Method: The annual blood production in the Khulna City Corporation (KCC) slaughterhouses was estimated, blood samples were collected, and blood meals were manufactured and characterized for their nitrogen content and other nutritional values. The best blood meal was sorted out, incubated in soil, and applied to spinach (Spinacea oleracea L.) to assess the effects of the final product on plant and soil health.Result: This investigation estimated the annual disposal of 58.62 tons of bovine blood from the KCC slaughterhouses.  The conventionally derived blood meal (BMc) attained the higher amount of primary nutrients (NPKS), while oven-dried blood meal (BMod) attained the higher amount of secondary nutrients (Ca and Mg), micronutrients (Fe, Cu, and Mn) and heavy metals (Cr, Pb, Ni). An increasing rate of blood meal incubation in soil increased available N and N-mineralization with an incubation time of up to 90 days. Blood meal application to spinach at a rate of 5 t/ha had evident higher productivity and better N-utilization efficiency although application rate above 5 t/ha declined crop performance. Conclusion:  The outcome of the study suggests that blood meal can be used as an organic source of nitrogen and the application of blood meal has manifold benefits if applied at a judicious rate preferably less than or equal to 5 t/ha.